2014
DOI: 10.2337/db13-1121
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 130 Receptor Signaling Mediates α-Cell Dysfunction in a Rodent Model of Type 2 Diabetes

Abstract: Dysregulated glucagon secretion accompanies islet inflammation in type 2 diabetes. We recently discovered that interleukin (IL)-6 stimulates glucagon secretion from human and rodent islets. IL-6 family cytokines require the glycoprotein 130 (gp130) receptor to signal. In this study, we elucidated the effects of a-cell gp130 receptor signaling on glycemic control in type 2 diabetes. IL-6 family cytokines were elevated in islets in rodent models of this disease. gp130 receptor activation increased STAT3 phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
(57 reference statements)
2
19
0
Order By: Relevance
“…Il6st, also known as glycoprotein 130 (gp130), is the β-subunit of the IL-6 cytokine receptor. A recent report showed that Il6st is required for IL-6-mediated activation of STAT3, and stimulation of glucagon secretion (CHOW et al 2014). Further, α-cell-specific deletion of Il6st resulted in protection from Streptozotocin-induced diabetes (CHOW et al 2014), suggesting that in the context of inflammation that accompanies T2D, Il6st may promote hyperglycemia by stimulating glucagon secretion from α-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il6st, also known as glycoprotein 130 (gp130), is the β-subunit of the IL-6 cytokine receptor. A recent report showed that Il6st is required for IL-6-mediated activation of STAT3, and stimulation of glucagon secretion (CHOW et al 2014). Further, α-cell-specific deletion of Il6st resulted in protection from Streptozotocin-induced diabetes (CHOW et al 2014), suggesting that in the context of inflammation that accompanies T2D, Il6st may promote hyperglycemia by stimulating glucagon secretion from α-cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that Il6st is required for IL-6-mediated activation of STAT3, and stimulation of glucagon secretion (CHOW et al 2014). Further, α-cell-specific deletion of Il6st resulted in protection from Streptozotocin-induced diabetes (CHOW et al 2014), suggesting that in the context of inflammation that accompanies T2D, Il6st may promote hyperglycemia by stimulating glucagon secretion from α-cells. Il6st is in the royalblue module, along with transcripts that are significantly enriched for the GO term, "positive regulation of cytokine production".…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation and functional aberration of these differential genes has also been studied (Baxter, 2008; Pihlajamäki et al, 2009; Jewell et al, 2010; Jowett et al, 2010; Nitert et al, 2012; Reddy et al, 2012; Chow et al, 2014; Liew et al, 2014; Neglia et al, 2014) in type 2 diabetes progression. The T2DM linked genes including ZEB1, USP16, IL6ST, ASPH, Eif4g1, RBL2, MEF2A, vapB, and SOS2 effect on pancreatic β-cells, peripheral glucose uptake in muscles, the secretion of multiple cytokines, β-cell gene expression, islet cells, β-cells chromatin and proliferation attenuation (Baxter, 2008; Jowett et al, 2010; Nitert et al, 2012; Chow et al, 2014; Liew et al, 2014). The genetic networks extended the analysis of transcripts to predict interactive gene signatures that have role in diabetes pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Another systems biology approach based on genome wide association studies explored the T2DM pathophysiology and insulin signaling genes (Jain et al, 2013). Similarly, the abnormal secretion of glucagon led to islet inflammation in T2DM and it has been seen the interleukin-6 is involved to stimulate the glucagon secretion (Chow et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the absence of IL6 is associated with decreased expression of iHSP70 in skeletal and cardiac muscle of mice challenged with LPS, although IL-6 seems not to be required for exercise-induced HSP production [134]. In addition, recent work has shown that IL-6 acts on α-cells by binding to GR130 receptors and (via STAT3) thus stimulating glucagon synthesis [135]. What is more, incubation of α-cells with IL-6 protects from cell death induced by a mixture of cytokines [IL-1β, TNFα and interferon γ (IFNγ )], consistent with previous observations under nutrient stress [124].…”
Section: Figurementioning
confidence: 97%